2011
DOI: 10.1111/j.1523-5378.2011.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Immunity Against Helicobacter pylori in the Absence of IL-17A

Abstract: Helicobacter pylori (H. pylori) is a gram negative bacterium that can cause diseases such as peptic ulcers and gastric cancer. IL-17A, a proinflammatory cytokine that can induce the production of CXC chemokines for neutrophil recruitment, has recently been shown to be elevated in both H. pylori-infected patients and mice. Furthermore, studies in mouse models of vaccination have reported levels significantly increased over infected, unimmunized mice and blocking of IL-17A during the challenge phase in immunized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
3
22
0
1
Order By: Relevance
“…pylori stomach infection and histopathology. An in vivo H. pylori gastric infection model system has been previously described (13,14,17,18). In this system, colonization efficiency is routinely Ͼ90% as determined by the percent of infected animals from which H. pylori can be recovered, either as viable bacteria and by testing for bacterial urease, oxidase, and catalase activities to confirm their identity as H. pylori, or by real-time RT-PCR for bacterial gene sequences (e.g., urease C).…”
Section: Methodsmentioning
confidence: 99%
“…pylori stomach infection and histopathology. An in vivo H. pylori gastric infection model system has been previously described (13,14,17,18). In this system, colonization efficiency is routinely Ͼ90% as determined by the percent of infected animals from which H. pylori can be recovered, either as viable bacteria and by testing for bacterial urease, oxidase, and catalase activities to confirm their identity as H. pylori, or by real-time RT-PCR for bacterial gene sequences (e.g., urease C).…”
Section: Methodsmentioning
confidence: 99%
“…This inflammation is dependent on CD4 + T cells[12], and many studies demonstrate that Th1, Th17, or both Th1 and Th17 immunity are required[10], [13], [14], [15], [16], [17], [18], [19]. Initial studies using mice deficient in the IL-12 family p40 subunit showed a lack of vaccine induced protection[18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…We now report that sublingual immunization with dmLT and H. pylori lysate antigens strongly increases IFN-␥ and IL-17A gene expression in the stomachs of mice and also the production of these cytokines by MLN and spleen cells after in vitro stimulation with H. pylori antigens. Effective induction of IL-17 is desirable when designing a vaccine against H. pylori infection, since one of the functions of IL-17 is to recruit neutrophils, which have been shown to be essential in reducing the bacterial loads in the stomachs of vaccinated mice (28), although DeLyria et al have reported that in mice immunized with H. pylori lysate antigens and CT, neutrophils can be recruited to the stomach after challenge independent of IL-17A (29). However, IL-17 has multiple roles, and we believe that its main function in H. pylori infection is to promote bacterial clearance by possibly recruiting bactericidal neutrophils and also to stimulate local IgA antibody formation (30).…”
Section: ⌬Ctmentioning
confidence: 99%